Determinants of the return spread on Chilean corporate bonds - Gregoire C., Jorge; Álvarez T., Carolina (Estudios de Administración, 2007)
The objective of this article is an empirical investigation on the factors that could explain the yield spread on corporate bonds, in the Chilean capital market. The econometric method of data panel is utilized, for a sample of corporate bonds during the period January 2000 to June 2005. The results obtained both for bonds with a short call option embedded and bonds without it, show that stock return and volatility, term structure of interest rates (level and slope) are significant factors, and also credit rating by independent firms, and bond maturity, all with the theoretical signs predicted.